Overcoming of radiation resistances - Friesen, C.; Hormann, I.; Roscher, M.; Bacher, S.; Miltner, E. (Nuklearmedizin - NuclearMedicine, 2010)
Despite good achievements in prevention and control, cancer is still a leading cause of death worldwide. The development of resistances against conventional treatment modalities is one of the main causes of failure in the treatment of cancer. Radio- and chemotherapies fail frequently due to intrinsic or acquired resistances in apoptotic signalling pathways or alterations in DNA-repair processes.Targeted radiotherapies employing α-particle-emitting radionuclides and Auger-emitting electrons are a promising approach in cancer treatment to break radio- and chemo – resistance by overcoming DNA-repair mechanisms and reversing deficient activation of apoptotic pathways in cancer cells.
Keywords: Cancer treatment; resistances; apoptosis; DNA-repair; α-emitter; Auger electrons